Theoretical Analysis of Two Collinear Cracks in an Orthotropic Solid under Linear Thermal Flux and Linear Mechanical Load. (9th February 2022) - Wu, Bing; Zhu, Bao-Yin; Song, Hao-Meng; Huang, Qiong-Ao
Abstract : This paper studies the problem of a cracked orthotropic solid subject to linear thermal flux and linear mechanical load. The proposed extended partially insulated crack model is employed to simulate two collinear cracks. Taking advantage of Fourier transform technique and superposition theory, the closed form of some physical quantities and fracture parameters is obtained. Some simple examples are employed to demonstrate dimensionless thermal conductivity (R c ) between the upper and below crack regions, and the proposed coefficient (ε ) has great effects on some physical quantities and fracture parameters.